COMPETENCE FORMING INTERDISCIPLINARY INTEGRATION IN TEACHING TECHNOLOGY - Abdullaeva Feruza (American Journals, 2025)
The study explores the development of interdisciplinary competence in teaching Technology as a school subject, emphasizing its significance within modern educational paradigms. The research provides a scientific analysis of the content of technology education, mechanisms of interdisciplinary integration, didactic foundations of the competence-based approach, and a system of skills formed in learners. The study highlights integrative-module methods, instructional strategies, and cognitive-activity approaches that enhance the effectiveness of interdisciplinary teaching. The results hold scientific and practical value for improving technology curricula and strengthening learners’ creativity and problem-solving competencies.
Keywords: Technology education, interdisciplinary integration, competence, didactic approach, problem-based learning, creativity.